The role of illicit, licit, and designer drugs in the traffic in Hungary. (June 2017) - Institóris, László; Hidvégi, Előd; Dobos, Adrienn; Sija, Éva; Kereszty, Éva M.; Tajti, László Balázs; Somogyi, Gábor Pál; Varga, Tibor
Highlights: Samples of 1252 suspected DUID drivers were analyzed in 2014–15 in Hungary. The ratio of positive cases was 79%, impairment was proved in 45–50% of them. Ratio: illicit drug: 58.7%, medication: 16.8%, SDD: 19.4%, synth. cannab.: 13.5%. Alcohol and drugs were simultaneously present in 10% of positive cases. The most frequent drugs were cannabis, amphetamine, and pentedrone. Abstract: The aim of this study was to investigate the prevalence and pattern of psychoactive substances among suspected DUID (Driving Under the Influence of Drugs) drivers in Hungary in 2014 and 2015. Blood and/or urine samples of 1252 suspected drivers (600 in 2014 and 652 in 2015) were analyzed for classical illicit and licit drugs, stimulant designer drugs (SDDs), and for synthetic cannabinoids, with 78.3% and 79.6% positive cases for at least one substance in 2014, and 2015, respectively. Impairment was proven in 39.2% (2014) and 35.7% (2015) of all drivers tested, based on the legal criteria of Hungary. Classical illicit drugs were found to be present in blood or urine of 89–61%, drivers tested. Drivers also tested positive for legal medications in 20–22%, SDDs in 21–28%, and synthetic cannabinoids in 15–19% of all cases. This indicates a drop in prevalence for classical illicit drugs and a slight but statistically non-significant increase for the other three substance groups. The distribution of drug types in each category were: [1] classical illicit drugs: cannabis (432), amphetamine (321), and cocaine (79); [2] medicines: alprazolam (94) and clonazepam (36); [3] SDDs: pentedrone (137) and α-PVP (33); [4] synthetic cannabinoids: AB-CHMINACA (46) and MDMB-CHMICA (30). The average age of illicit drug and SDD users was 30 years, while legal medications users were 36 years old on average, and the mean age of synthetic cannabinoid users was 26.5 years. The presence of both alcohol and at least one drug in samples was found in about 10% of the cases, both years. The ratio of multi-drug use was 33.0% in 2014 and 41.3% in 2015. Compared to former years the number of drivers who tested positive for drugs doubled in Hungary, but it is still low compared to alcohol positive cases. The relatively low detected rate of DUID can be explained by (1) combined alcohol consumption masking drug symptoms, (2) the absence of road-side tests for illicit and designer drugs and, (3) police officers not adequately trained to recognize milder symptoms of impairment. Targeted education of police officers, prompt medical examination and the use of a symptom-focused on-site survey, could improve the efficacy of DUID investigations. Our findings are not comparable with drug consumption habits of the general driving population. The last roadside survey (DRUID EU-6 Project) was performed in Hungary in 2008–2009, prior to the mass spreading of designer drugs. As their appearance has drastically changed the pattern of drug consumption of the population, a new roadside survey, targeting general drivers, would be necessary.